Design, construction and evaluation of a solar dryer for Ataulfo mango - Iglesias Díaz, Roilan; José Gómez, Reynaldo Alonso; Lastres Danguillecourt, Orlando; López de Paz, Pascual; Farrera Vázquez, Nein; Ibáñez Duharte, Guillermo Rogelio (Revista Mexicana de Ciencias Agrícolas, 2017)
The design, construction and evaluation of a solar dryer for Ataulfo mango harvested in the Soconusco region in the state of Chiapas is reported. In this region, 15% of the mango is lost due to its super production and because it does not have a postharvest conservation method. For the design, the specifications of the product to be dried, the registration of the climatic conditions of the place and the experimental drying tests carried out were used in the UNICACH. The proposed methodology is based on the systematic combination of the application of the basic concepts of design and general rules of heat and mass transfer, presenting the results of these calculations in a table. The average vacuum and humidity values in the drying chamber of 5% and 45 °C respectively were obtained from the vacuum evaluation of the dryer. The average temperature of the ambient air was 25 °C and the average solar radiation of 500 W m-2. The drying time was 8 hours, drying to 8.4% from an initial humidity of 80%. The curves are presented in vacuum evaluation; In addition to the variation of weight, humidity and free moisture of the handle with respect to time. It was demonstrated that it is possible to give post-harvest treatment of the Ataulfo mango and take advantage of the one that is lost in the fields. This solar dryer design is very flexible in its operation.
Keywords: design, mango conservation, solar dehydration